2005
DOI: 10.1016/j.febslet.2005.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of hereditary amyloid β‐protein variants in the presence of favorable gangliosides

Abstract: The mechanisms underlying regional amyloid b-protein (Ab) deposition in brain remain unclear. Here we show that assembly of hereditary variant Dutch-and Italian-type Abs, and Flemish-type Ab was accelerated by GM3 ganglioside, and GD3 ganglioside, respectively. Notably, cerebrovascular smooth muscle cells, which compose the cerebral vessel wall at which the Dutch-and Italian-type Abs deposit, exclusively express GM3 whereas GD3 is upregulated in the co-culture of endothelial cells and astrocytes, which forms t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
80
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(85 citation statements)
references
References 26 publications
3
80
0
Order By: Relevance
“…Furthermore, the presence of these substitutions in CAA mutant forms of A␤ may induce conformational changes in the monomeric peptide and/or oligomeric assemblies that suppress or enhance further assembly and deposition in the parenchyma or cerebral vasculature, respectively. Consistent with this idea, it has been shown previously that the GM3 ganglioside, which is present in cultured cerebrovascular cells and in cerebral vessels, preferentially enhances fibrillar assembly of CAA mutant A␤ (73,74). Lastly, CAA mutant A␤ peptides show significantly impaired clearance from the brain via transport across the blood-brain barrier into the circulatory system and perivascular drainage to the cerebrospinal fluid (66,75).…”
Section: Discussionsupporting
confidence: 63%
“…Furthermore, the presence of these substitutions in CAA mutant forms of A␤ may induce conformational changes in the monomeric peptide and/or oligomeric assemblies that suppress or enhance further assembly and deposition in the parenchyma or cerebral vasculature, respectively. Consistent with this idea, it has been shown previously that the GM3 ganglioside, which is present in cultured cerebrovascular cells and in cerebral vessels, preferentially enhances fibrillar assembly of CAA mutant A␤ (73,74). Lastly, CAA mutant A␤ peptides show significantly impaired clearance from the brain via transport across the blood-brain barrier into the circulatory system and perivascular drainage to the cerebrospinal fluid (66,75).…”
Section: Discussionsupporting
confidence: 63%
“…22) Thus, it appears that the Flemish mutation in the Aβ peptide inhibits secondary structure formation upon membrane interaction and self-assembly, both of which are critical steps in the initial nucleation resulting in amyloid plaques. Other important issues, however, remain to be defined including the observation that the fibril formation of the Flemish mutant appears to be specifically promoted through its interaction with ganglioside GD3, which is abundant in vascular walls, 17) and the fact that the A21G mutation appears to inhibit aggregation of Aβ 1-42 more effectively than that of Aβ in the clinical states. 19) Structural analyses of the putative interactions of the Flemish and other Aβ variants with their specific gangliosides, and the conformational effects of the A21G substitution on its different isoforms of Aβ are currently in progress.…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12][13][14] These hereditary Aβ mutants exhibit different physicochemical properties, such as aggregation propensities and ganglioside specificities, which are likely to be associated with AD pathogenesis. [15][16][17][18] Among the Aβ variants, the Flemish mutant has unique properties, such as the lowest aggregation propensity, and undergoes progressive deposition in vascular walls resulting in strokes and formation of unusually large senile plaque cores. 15,[19][20][21] Moreover, in contrast to other familial AD cases with predominant Aβ 1-42 deposition in the brain, the deposits of patients with Flemish AD contain primarily the Aβ 1-40 isoform.…”
mentioning
confidence: 99%
“…The exclusive collection of fibrillar amyloid in the cerebral vasculature suggests that specific factors in this compartment may enhance CAA mutant Aβ fibril assembly and deposition. For example, we recently showed that GM3 ganglioside, which is abundantly found in cultured cerebrovascular cells and in isolated cerebral vessels but not in the brain parenchyma, selectively promotes fibrillar assembly of CAA mutant forms of Aβ (Yamamoto et al, 2005). In any case, the restriction of fibrillar amyloid predominantly to the cerebral vasculature accurately mirrors the site of fibrillar Aβ deposition in patients with the Dutch-type or Iowa-type familial CAA disorders (Grabowski et al, 2001;Maat-Schieman et al, 2004).…”
Section: Discussionmentioning
confidence: 99%